Sumac extract as a natural preservative in mayonnaise: Effects on lipid oxidation, microbial growth, physicochemical, rheological, and sensory characteristics - Mohammad Shayan Nessabian; Samar Mansouripour; Yousef Ramezan (Journal of Agriculture and Food Research)
The present study was conducted to evaluate the effect of sumac extract (SE) as a natural antioxidant and antimicrobial agent on the quality characteristics of low-fat mayonnaise during 63 days of storage. The SE was used at levels of 1 % (SE1%), 3 % (SE3%), and 5 % (SE5%) in the formulations. The two control treatments were produced with chemical preservatives (C1) and without preservatives (C2). The SE caused a significant decrease in peroxide and anisidine values compared to controls after 63 days (4.73–5.77 meq/kg vs. 6.33–6.73 meq/kg for peroxide values, and 6.29–11.21 vs. 12–13.60 for anisidine values, P < 0.05). The higher inhibitory effects of SE on microbial growth in mayonnaises were revealed after 63 days, where the total viable count declined from the highest value (36.5 log CFU/g) in C2 to the lowest count (12 log CFU/g) in SE5%. The yeasts and molds count in SE1% (4.5 log CFU/g) were lower than the counts of 20.5 log CFU/g and 23.5 log CFU/g observed in C1 and C2, respectively. Moreover, significant reductions in Lactic Acid Bacteria were observed in SE-enriched treatments (P < 0.05). The phenolic and flavonoid contents of mayonnaise treatments besides antioxidant capacity were enhanced by increasing SE concentrations. However, the lowest storage modulus and complex viscosity were observed in SE5%. The highest overall acceptance belonged to C1 followed by SE1% at the end of storage. Finally, SE has the potential to be used as a natural preservative in mayonnaise.